Perubahan Perilaku Pedagang Pasca Revitalisasi Blok III Pasar Raya Padang - Almuttaqin Suddana (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2019)
Article attempts to describe and explain in detail the changes in traders' behavior afterRevitalization of Blok III Pasar Raya Padang. Informants were selected using purposive sampling techniqueand in data collection used observation techniques and in-depth interviews. The results showed an increasinglygood physical market change such as the presence of merchant zoning, market floors that had been usingceramics, increasingly good lavatories, better prayer rooms, extensive merchant stalls, cleanliness and marketsecurity. Market changes bring changes in the behavior of traders both in serving buyers such as hours of goingand going home trading, strategies to serve buyers and how to increase merchant merchant turnover. Thebetter and more organized physical changes make the behavior of traders more orderly and cleaner. There aremany ways for traders to dispose of trash, such as throwing trash into the trash can, putting it in a sack, andputting it next to the tavern so that it is not included. Market revitalization influences the relationship betweentraders before being revitalized which is increasingly distant due to the distance between old traders.